PENYELESAIAN KREDIT MACET DALAM PERJANJIAN KREDIT PEMILIKAN RUMAH (KPR) - Prabowo, Shidqon (Diponegoro Private Law Review, 2019)
ABSTRACT  This research was carried out in semarang,  describing how the form of settlement bad credit in house ownership credit agreement.The research method used in this study is an empirical juridical, conducted by examining existing rules and theories with reality or facts. the results of the first study,  efforts to resolve bad credit in a house ownership credit agreement (KPR) at Semarang State Savings Bank. Engagement that is able to provide legal protection to binding parties in the agreement.  Keywords : Legal protection of bad credit. Settlement of bad credit.